Community Meaning-Making of PT INALUM’s CSR Program in MSME Development in Batu Bara Regency: A Stuart Hall Reception Analysis - Putri Balqis Maharani Siregar; Indira Fatra Deni (Ali Institute of Research and Publication, 2026)
This study examines community meaning-making of the Corporate Social Responsibility (CSR) program implemented by PT Indonesia Asahan Aluminium (PT INALUM) in the development of Micro, Small, and Medium Enterprises (MSMEs) in Batu Bara Regency. It aims to describe how the community interprets the CSR program and to identify the factors influencing such interpretations. This study employed a descriptive qualitative method with a case study approach. Data were collected through in-depth interviews, observation, and documentation involving five informants consisting of assisted MSME actors and surrounding community members. The data were analyzed using the Miles, Huberman, and Saldaña model through data reduction, data display, and conclusion drawing. The findings indicate that most informants interpreted PT INALUM’s CSR program positively because it was perceived to provide benefits for business development, environmental awareness, and social relations within the community. Based on Stuart Hall’s reception theory, the informants’ interpretations tended to fall within the dominant-hegemonic position, although elements of a negotiated position also appeared in the form of expectations for more continuous mentoring and program socialization. These interpretations were influenced by perceived program benefits, company communication, community involvement, and local social conditions. This study provides an empirical overview of community reception of CSR programs in the context of MSME development, without intending to measure the program’s impact quantitatively.